2021
DOI: 10.1093/tropej/fmab062
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestations of Pediatric Acute COVID Infections: A Single Center Experience

Abstract: Background Coronavirus disease 2019 (COVID-19) usually leads to a mild infectious disease course in children, while serious complications may occur in conjunction with both acute infection and neurological symptoms, which have been predominantly reported in adults. The neurological complications in these patients vary based on patient age and underlying comorbidities. Data on clinical features, particularly neurological features, and prognostic factors in children and adolescents are limited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 45 publications
3
33
1
Order By: Relevance
“…Few reports of real-time PCR (RT-PCR) SARS-CoV-2-positive children experiencing epileptic seizures are currently available in the literature (29,(38)(39)(40)(41). In our cohort, 2 patients were presented at the ED with seizures; one experiencing seizures re-exacerbation despite being previously well-controlled with a single ASM, the other with newly-onset seizure within the context of a malacic region due to a previous ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports of real-time PCR (RT-PCR) SARS-CoV-2-positive children experiencing epileptic seizures are currently available in the literature (29,(38)(39)(40)(41). In our cohort, 2 patients were presented at the ED with seizures; one experiencing seizures re-exacerbation despite being previously well-controlled with a single ASM, the other with newly-onset seizure within the context of a malacic region due to a previous ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, neurological findings are more common in obese patients in the literature. [6,9–12,15,23,26,53–55]…”
Section: Discussionmentioning
confidence: 99%
“…Kurd et al ( 81 ) pointed out that seizures occurred in an early phase once children were infected with SARS-CoV-2 and may be the main manifestation of acute COVID-19 in children (11/175). Similarly, Dilber et al ( 82 ) reported results of Turkey, where seizures (18/382) were the most common cause of hospitalization in children with COVID-19. In addition to the incidence of seizures attracted the interest from neurologists, the management of seizures also poses a significant challenge to neurologists and caregivers.…”
Section: Discussionmentioning
confidence: 84%